2016
DOI: 10.11604/pamj.2016.23.100.7879
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of default to fully completion of immunization among children aged 12 to 23 months in south Ethiopia: unmatched case-control study

Abstract: IntroductionImmunization is a cost effective interventions of vaccine preventable disease. There is still, 2.5 million children die by vaccine preventable disease every year in developing countries. In Ethiopia, default to fully completion of child immunization is high and determinants of default to completions are not explored well in the study setting. The aim of the study was to identify determinants of default to fully completion of immunization among children between ages 12 to 23 months in Sodo Zurea Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 12 publications
3
31
1
1
Order By: Relevance
“…Studies have shown that maternal education, socioeconomic status, and maternal service utilization during antenatal care (ANC), during delivery, and postnatal care associated with child immunization [ 10 – 14 ]. Additionally, factors such as media exposure, perceptions of vaccination, child’s place of birth (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that maternal education, socioeconomic status, and maternal service utilization during antenatal care (ANC), during delivery, and postnatal care associated with child immunization [ 10 – 14 ]. Additionally, factors such as media exposure, perceptions of vaccination, child’s place of birth (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, factors such as media exposure, perceptions of vaccination, child’s place of birth (e.g. health facility), and region of residence also influence the immunization coverage among children [ 10 – 13 ]. Furthermore, the application of multilevel modeling has shown that community/contextual characteristics such as region or province of residence [ 12 , 15 , 16 ], community maternal education [ 15 , 16 ], level of ANC utilization [ 12 ], level of the institutional delivery [ 15 ], and community poverty level [ 12 ] are important determinants of immunization service utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies reported determinants of immunization coverage in Ethiopia, they are not consistent and varied across the country. The reported determinants include ANC and PNC coverage, knowledge on age of a child to be vaccinated, parents formal education, place of delivery, residence, traveling time to health facilities, TT vaccination, family size, household wealth status, and marital status [19][20][21][22][23]. Thus, the current work aims at identifying relevant studies and summarizing major predictors of immunization coverage in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…The 2016 EDHS report indicated that vaccination coverage in Ethiopia was low that only 39% of children received all the basic childhood vaccinations [ 6 ]. Studies have shown that maternal education, socioeconomic status, antenatal care, delivery, postnatal care, media exposure, perceptions of vaccination, child's place of birth, and region of residence also influence childhood vaccination status [ 7 – 11 ]. Furthermore, the application of multilevel modeling has helped to assess the community/contextual characteristics, such as the region or province of residence [ 9 , 12 , 13 ], community maternal education [ 12 , 13 ], level of ANC [ 9 ], institutional delivery service utilization [ 12 ], and community poverty level [ 9 ], on childhood vaccination service utilization.…”
Section: Introductionmentioning
confidence: 99%